Oficina de sistemas. (UNED, 2024)
Sentadas de izquierda a derecha Xinia Zeledón Morales, Guiselle Hidalgo Molina y Carmen María Gutiérrez Yglesias, de pie de izquierda a derecha Mirna Fonseca Alvarez, Lorena Palma, Zayra Flores Marchena, Nuria Rodríguez, Manuel Murillo, Rodolfo Artavia Jacks y Donobal Thompson